2018
DOI: 10.1007/s10484-018-9389-1
|View full text |Cite
|
Sign up to set email alerts
|

Resting Heart Rate Variability and the Effects of Biofeedback Intervention in Women with Low-Risk Pregnancy and Prenatal Childbirth Fear

Abstract: Anxiety about labor in women at the end of pregnancy sometimes reaches levels that are clinically concerning. We investigated whether low-risk pregnant women with childbirth fear during the last trimester demonstrate specific findings with regard to resting heart rate variability (HRV) and examined whether HRV biofeedback can reduce this fear and alter resting HRV. We measured the levels of childbirth fear (Wijma delivery expectancy/experience questionnaire, W-DEQ) and resting HRV indexes in 97 low-risk pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Twelve studies examined alternative interventions, including relaxation (e.g. guided relaxation, meditation/mindfulness, hypnobirthing; Baleghi, Akerdi, & Pasha, 2016 ; Bulez et al, 2019 ; Byrne, Hauck, Fisher, Bayes, & Schutze, 2014 ; Fisher et al, 2012 ; Hunter et al, 2011 ; Pour-Edalati et al, 2019 ), exercise ( n = 2; Guder, Yalvac, & Vural, 2018 ; Guszkowska, 2014 ), art therapy ( n = 2; Sezen & Ünsalver, 2019 ; Wahlbeck, Kvist, & Landgren, 2018 ) or group psychodynamic (Saisto, Toivanen, Salmela-Aro, & Halmesmäki, 2006 ), role play (Navaee & Abedian, 2015 ) and heart rate monitoring (Narita, Shinohara, & Kodama, 2018 ). Ten studies had control groups; no studies were RCTs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve studies examined alternative interventions, including relaxation (e.g. guided relaxation, meditation/mindfulness, hypnobirthing; Baleghi, Akerdi, & Pasha, 2016 ; Bulez et al, 2019 ; Byrne, Hauck, Fisher, Bayes, & Schutze, 2014 ; Fisher et al, 2012 ; Hunter et al, 2011 ; Pour-Edalati et al, 2019 ), exercise ( n = 2; Guder, Yalvac, & Vural, 2018 ; Guszkowska, 2014 ), art therapy ( n = 2; Sezen & Ünsalver, 2019 ; Wahlbeck, Kvist, & Landgren, 2018 ) or group psychodynamic (Saisto, Toivanen, Salmela-Aro, & Halmesmäki, 2006 ), role play (Navaee & Abedian, 2015 ) and heart rate monitoring (Narita, Shinohara, & Kodama, 2018 ). Ten studies had control groups; no studies were RCTs.…”
Section: Resultsmentioning
confidence: 99%
“…One exercise intervention including yoga, Pilates and body ball found no impact on FOC (Guszkowska, 2014 ) whereas another Pilates course was found to reduce FOC (Guder et al, 2018 ). Lastly, heart rate variability biofeedback was associated with lower FOC over time (from 32–34 to 36–67 weeks) (Narita et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…There are inconsistent findings about these associations in the existing literature. In one study, no significant association was found between fear of childbirth and HRV among pregnant women at 32 to 34 weeks of gestation [ 47 ]. However, higher self-perceived stress and lower HRV was reported among pregnant women between 12 and 30 weeks of gestation [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…14 studies focused on "fear of childbirth" as an outcome (Abdollahi et al, 2020;Airo (Toivanen) et al, 2018;Amiri et al, 2019;Andaroon et al, 2017;Boryri et al, 2018;Boz et al, 2020;Firouzan et al, 2020;Haapio et al, 2017;Hildingsson et al, 2019;Irmak Vural & Aslan, 2019;Kacperczyk-Bartnik et al, 2019;Karabulut et al, 2016;Klabbers et al, 2019;Kordi et al, 2017;Larsson et al, in press;Mary et al, 2017;Munkhondya et al, 2020;Narita et al, 2018;Nieminen et al, 2016;Rahmani et al, 2019;Rondung et al, 2018;Rouhe et al, 2015b;Shahsavan et al, 2020;Swift et al, in press;Uçar & Golbasi, 2019).…”
Section: Outcome Variablesmentioning
confidence: 99%
“…Boryri et al (2018) and Khojasteh et al (2016) studied the effect of guided imagery on FOC and pregnancy related anxiety and found a significant decrease of fear of delivery on anxiety though guided imagery. Narita et al (2018) studied the effect of a heart rate variability (HRV) biofeedback intervention on fear of childbirth and found that FOC was significantly reduced in women who performed HRV biofeedback. Contrary to this result, van der Zwan et al ( 2019), who studied a heart rate variability (HRV)-biofeedback intervention combined with a stress-reducing intervention, did not find significant long-term improvements in the HRV-biofeedback condition.…”
Section: Categories Of Interventionsmentioning
confidence: 99%